Optimization of dune sand-based mixture material for pavement design. Issue 11 (28th July 2022) - Moulay Omar, Hassan; Mekerta, Belkacem; Jarno, Armelle; Imanzadeh, Saber; Alem, Abdellah; Taibi, Said
Abstract: Many geotechnical problems involve pavements in Algerian arid regions; the main among them being related to the scarcity of standard materials. Recently, numerous studies were carried out on the valorization of Saharan local materials for pavement design. In this context, dune sand, tuff and quarry waste are promising alternatives. In this study, the design of experiments was used to optimize formulations to meet the current unconfined compressive strength ( UCS ) recommendations according to grading distribution. For the studied local material, the use of UCS criterion extended the valid domain of formulations to poorly graded materials where the amount of dune sand could reach 54.5%. An optimal formulation was proposed and tested, composed of 46% dune sand, 36% tuff, 11% quarry waste and 7% water, fulfilling all current recommendations related to the pavement design in the Sahara region. Finally, the results show that the design of experiments can be a useful tool to optimize mixture formulations and valorize local materials such as dune sand.